ANALISIS KINERJA PENYULUH TERHADAP PEMBERDAYAAN KELOMPOK USAHA PETERNAKAN SAPI DI DESA TONDEGESAN KECAMATAN KAWANGKOAN KABUPATEN MINAHASA - Sondakh, Indah Th.P; Malingkas, J A; Lainawa, J; Lenzun, G D (ZOOTEC, 2019)
ABSTRACTANALYSIS OF INSTRUCTOR PERFORMANCE TO EMPOWERING CATTLE BREEDING BUSINESS GROUP AT TONDEGESAN VILLAGE OF KAWANGKOAN DISTRICT. The purpose of this study was to analyze the performance of instructors on empowerment of cattle business groups in Tondegesan Village, Kawangkoan District, Minahasa Regency. This research was carried out by using data miles and huberman analysis which was carried out when the data collection took place in the field. The study population was all members of the serentape business group. The sampling method for farmers is based on indications to assess performance, namely productivity, responsiveness, and responsibility. The results showed that the performance of extension agents was mostly in the successful category. The success of the instructor's performance in the productivity level is in the successful category with a percentage of 93.33%, in the level of responsiveness in the successful category with a percentage of 73.33%, and the level of responsibility in the successful category with a percentage of 93.33%. Based on the research,concluded that the performance of the instructor towards the empowerment of business groups in the village of Tondegesan, Kawangkoan Subdistrict which was measured in terms of productivity, responsiveness and responsibilitysuccessful.Keywords: Performance, Extension, Empowerment